1987
DOI: 10.3171/jns.1987.67.4.0525
|View full text |Cite
|
Sign up to set email alerts
|

The rCBF response to Diamox in normal subjects and cerebrovascular disease patients

Abstract: Age-related norms for the regional cerebral blood flow (rCBF) response to Diamox (acetazolamide) were based on studies of 55 normal subjects at rest and on studies of 33 of these 55 normal subjects following an intravenous injection of Diamox (22 mg/kg). After the Diamox injection, rCBF increased at all locations measured in all subjects. On average, rCBF increased 1.7 times. The following were found for rCBF in both resting and Diamox-treated subjects: 1) rCBF decreased significantly with increasing age; 2) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
52
1

Year Published

1989
1989
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(56 citation statements)
references
References 27 publications
3
52
1
Order By: Relevance
“…Inhibition of carbonic anhydrase causes carbonic acidosis, which induces a considerable increase in CBF. 23 ACZ is safe to administer and is generally well tolerated. Systemic blood pressure, heart and respiratory rates, arterial pH, arterial CO 2 pressure, and CMRO 2 are unaffected.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Inhibition of carbonic anhydrase causes carbonic acidosis, which induces a considerable increase in CBF. 23 ACZ is safe to administer and is generally well tolerated. Systemic blood pressure, heart and respiratory rates, arterial pH, arterial CO 2 pressure, and CMRO 2 are unaffected.…”
mentioning
confidence: 98%
“…Most common side effects are acute and transient, including transient circumoral numbness, paresthesias, malaise, and headache. 23,24 Reversible pontine ischemia caused by ACZ challenge has been discussed in a case report 25 ; however, Piepgras et al 26 reported no acute ischemic sequelae in more than 1000 studies with the use of ACZ.…”
mentioning
confidence: 99%
“…8,9 As a result, ACZ-challenged single-photon emission CT (SPECT) increases the contrast in radioactivity levels observed between regions of adequate vascular reserve and those of inadequate reserve. Cerebrovascular reserve (CVR) obtained by using SPECT provides important information on hemodynamic status in patients with chronic cerebrovascular occlusive diseases.…”
mentioning
confidence: 99%
“…Acetazolamide is a potent cerebral vasodilator (Mithoefer et aI., 1957) and is increasingly being used to assess hemodynamic reserve in the brain in combination with 133Xe inhalation, cold Xe com puted tomography (CT), single photon emission computed tomography (SPECT), or transcranial Doppler ultrasonography (Vorstrup et al , 1986;Sullivan et al, 1987;Sorteberg et al, 1989;Rogg et al , 1989;Knop et aI. , 1992;Hasegawa et al , 1992;Chimowitz et al , 1993).…”
mentioning
confidence: 99%